HUKUMAN KEBIRI KIMIA (CHEMICAL CASTRATION) UNTUK PELAKU KEKERASAN SEKSUAL PADA ANAK DITINJAU DARI KEBIJAKAN HUKUM PIDANA - Kristina Sitanggang; Madiasa Ablisar; Muhammad Ekaputra; Suhaidi Suhaidi (Universitas Sumatera Utara, 2018)
ABSTRACT Case of child abuse that committed by the nearest people with the children is a concerned condition. The environment and people around the children should teach, protect, educate and direct them to grow up and develop into a good child. In fact, the immediate environment like parents or family and teacher even become the parties who damage the mental and future of the children throught the unlaws act. This case is a form of human rights violation. It is not only to seize the unsurpation of security and protection but a victim also lose the right to live a physical and spiritual life, the rights to be free from torture or degrading treatment of human dignity and even loss their rights to life. Based on this case, the government conducted a criminal law policy through the provisions of the formulation of issuing government regulation in lieu of Law number 1 of 2016 which was then agreed by the legislative into the Law number 17 of 2016 which regulates the act of chemical castration for pedophile. Chemical castration is done by inserting antiandrogen chemicals, pills or injections into a person's body to weaken the hormone testosterone. Simply, the chemicals that are inserted into the body will reduce even eliminate libido or sexual desire. Chemical castration actions regulated in the provisions of law number 17 of 2016 is a form of punishment that is not in accordance with the criminal law policy in Indonesia, which criminal law policy in Indonesia is based on the provisions of Pancasila and the 1945 constitution. Chemical castration actions formulated in Article 81 paragraph (7) can be said is not in accordance with the values of Pancasila especially the first principle, a divinity that is an ultimate unity and the second principle, a just and civilized humanity Keyword : Punishment, Chemical Castration, Criminal Policy